Perspektif Islam Terhadap Manajemen Sumber Daya Manusia - Chusnul Rahmawati; Erika Nurhayani; Hilwa Karimah; Quanita Elisya; Yayat Suharyat (Pusat Riset dan Inovasi Nasional, 2023)
Human resource management (HRM) is an important component in any organization or business. The effectiveness of HR management will have an impact on the company's performance and output. In an Islamic perspective, effective HR management should be built on ideas that uphold Islamic ideals. Allah Almighty has given responsibility to man to manage human resources as effectively as possible. This is related to the idea of trust, which states that everyone is responsible for the property that Allah Almighty has entrusted to him. Man is assigned to use human resources as efficiently as possible by Allah SWT. This relates to the concept of amanah, which states that each individual is responsible for the material possessions that Allah Almighty has given them. Therefore, it is very important to apply justice and kindness in managing human resources. The list of books and articles in this review does not provide a comprehensive picture. Although these restrictions are sufficiently mitigated by the selection of different authors and publications, the results may be improved by a more thorough study. In many types of conflict, including war, religion has been shown to be a motivating factor in demonstrating human commitment and devotion. Knowing how religion functions in business can help develop the potential of HRM. A brief review of Islam's place in business, particularly in HRM, has the potential to have a significant impact.